Fish passage developments for small-bodied tropical fish: field case-studies lead to technology improvements. Issue 1 (2nd January 2019) - Marsden, Tim; Stuart, Ivor
Abstract: In tropical coastal lowland rivers, there are frequently biodiverse upstream migrations of post-larval and juvenile diadromous fish from estuaries into freshwater. Tidal barriers completely block major migratory pathways for these fish and have contributed to major losses of freshwater biodiversity. In northern Australia, early efforts to improve tropical river fish passage with salmonid-style fishways completely failed. Since the mid-1990s, low gradient vertical-slot and rock fishways improved fish passage but the smallest and most abundant fish (i.e. from 10 to 100 mm long) often still failed to ascend. Since the mid-2000s, there was a paradigm shift in hydraulic design criteria for new fishways, with a renewed focus on: (i) low turbulence, (ii) maximized roughness and hydraulic boundary layers to optimise fish ascent. We used a combined methodology, firstly developing a conceptual model of fish movement to inform fishway design criteria, secondly tabulating past and present fishway design criteria, and thirdly conducting a series of brief field case-studies, at tidal barriers in tropical rivers for new technical and rock fishways. Our objective was to evaluate the success of these new designs for passage of very small (from 9 mm long) diadromous fish on low head barriers (i.e. <3 m high). We conclude that while there have been improvements in passage of small-bodied fish at tidal barriers further experimental work is still needed to test and refine current ecohydraulic fishway design criteria.